INFLUENCE OF STREAMBED HYDRAULIC CONDUCTIVITY ON SOLUTE EXCHANGE WITH THE HYPORHEIC ZONE - Ryan R.J.; Boufadel M.C. (My University, 2006)
A conservative solute tracer experiment was conducted in Indian Creek, a small urban stream in Philadelphia, Pennsylvania to investigate the role of subsurface properties on the exchange between streamwater and the hyporheic zone (subsurface surrounding the stream). Sodium Bromide (NaBr) was used as a conservative tracer, and it was monitored in the surface water at two stations and in the upper bed sediments (shallow hyporheic zone extending from 7.5 to 10 cm below the streambed). The hydraulic conductivity (K) of the upper bed sediments and the lower bed sediments (10–12.5 cm below the streambed) was measured in situ. High tracer concentrations were observed in the upper layer at locations where the hydraulic conductivity of the upper layer was larger than that of the lower layer. Low concentrations in the upper layer were observed in the converse case. A statistically significant relationship between the mass retained in the upper layer and the difference of K values between layers was observed.
Keywords: HYPORHEIC EXCHANGE; HYDRAULIC CONDUCTIVITY; STREAMBED HETEROGENEITY; INDIAN CREEK; PHILADELPHIA; PENNSYLVANIA; USA